Natural language processing: python and NLTK - Nithin Hardeniya; Jacob Perkins; Deepti Chopra; Nisheeth Joshi; Iti Mathur (U K Packt Publishing, 2016)
This is not for loan and to transferred to computational linguistics department for a short period.
Keywords: Natural Language Processing; Python; NTLK; Speech Language Processing; Computational Linguistics